PERSEPSI PESERTA DIDIK TENTANG KEPRIBADIAN GURU BK DALAM PELAKSANAAN KONSELING PERORANGAN (Studi terhadap Peserta Didik Kelas VIII dan IX di SMP Negeri 25 Padang) - -, Musbinti - (Bimbingan dan Konseling, 2014)
This research is motivated by the conditions encountered in the field that the implementation of individual counseling is not as expected, because there are students who are reluctant to do individual counseling. The study aimed to describe: 1) Counselor personality on aspects of psychological health, 2) Counselor personality on aspects trustworthy, 3) Counselor personality on aspects of honesty, 4) Counselor personality on aspects of warmth, 5) Counselor personality on aspects patience. This research is descriptive quantitative. The study population was a student of class VIII and IX were never implement individual counseling in Champaign Junior High School 25 Padang totaling 314 and samples 35 learners. Results of the study: 1) Counselor personality on aspects of psychological health categorized well enough, 2) Counselor personality on aspects of trustworthy categorized quite well, 3) Counselor personality on aspects of honesty categorized quite well, and 4) Counselor personality aspects of warmth well categorized, 5) Counselor personality on aspects of patience categorized quite well.